The Effect of Work Stress and Job Satisfaction on Employee Performance of Non-Medical at Santa Maria Hospital - Rini Wijayaningsih; Widi Winarso; Hartanti Hartanti; Yani Restiyani Widjaja (Greenation International Journal of Economics and Accounting, 2026)
Study This aims to determine whether Job Stress and Job Satisfaction are related in general. simultaneous and Partial has a significant effect on employee performance. The population in this study was all employees of the non-medical House Sick Santa Maria Which address Jl. Raya Bantargebang-Setu No. 119 RT 002 RW 006 Padurenan Village, Mustika Jaya District, Bekasi City, West Java 17156, totaling 60 respondents. Based on the results of the study, it states that factors that influence performance exist. This is evidenced by the multiple linear regression equation obtained, namely Y = 7.963 + 0.210X₁ + 0.724X₂. Simultaneously, the results obtained from this study are that the variables of work stress and job satisfaction have a significant effect on employee performance variables, with the results showing that f count > f table of 35.283 f count > f table 3.156. Partially, the results show that variables stress Work influential and significant to performance, with results mark Which show t count 3.119 > t table 2.002 and sig. value 0.003 < 0.05 and job satisfaction variable also has an influence and is significant to performance with the results that show t count as big as 7,297 > 2,002 and sig. value 0.000 < 0.05.